Regionalising International Refugee Law in the European Union: Democratic Revision or Revisionist Democracy? - McAdam, Jane (Victoria University of Wellington Law Review, 2007)
This paper questions whether the process of harmonisation of the European Union’s asylum laws has strengthened the region’s commitment to international law and international standards, or has instead diluted them in order to accommodate regional (and domestic "democratic") concerns about forced migration. Harmonisation has taken place in a political environment that is suspicious of asylum seekers, that seeks restrictive entrance policies and that is wary of large numbers of refugees. This paper argues that such factors have heavily influenced the scope of the common asylum laws – who is eligible for protection – and the rights to which beneficiaries are entitled – what that protection actually is. It looks in particular at the confinement of protection to "third country nationals", a restriction which contravenes the 1951 Refugee Convention and denies international protection to groups within the EU such as the Roma, whose discrimination is welldocumented and has historically led to many being recognised as refugees. Furthermore, the paper considers that the EU citizen’s right to free movement is not synonymous with a right to residence, and is especially complicated for nationals of the 12 new accession States. It argues that harmonisation has occurred at the expense of a comprehensive and systematic analysis of international law, responding instead to "democratic" political compromise and pragmatism.